2004
DOI: 10.1056/nejmoa032736
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Positive-Pressure Ventilation for Respiratory Failure after Extubation

Abstract: Noninvasive positive-pressure ventilation does not prevent the need for reintubation or reduce mortality in unselected patients who have respiratory failure after extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
437
8
72

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 768 publications
(534 citation statements)
references
References 30 publications
17
437
8
72
Order By: Relevance
“…However few studies have demonstrated the efficacy of non-invasive ventilation after weaning from invasive ventilation for acute respiratory failure [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…However few studies have demonstrated the efficacy of non-invasive ventilation after weaning from invasive ventilation for acute respiratory failure [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable variation amongst studies reporting the outcome of BiPAP in the setting of acute respiratory failure. [82][83][84] In theory, BiPAP should minimize the decline in lung volume after surgery and may reduce pulmonary com-plications, but this possibility has not been studied. It has been shown that the use of CPAP may decrease the incidence of tracheal reintubation and other severe complications in patients who develop hypoxemia after elective major abdominal surgery.…”
Section: Non-invasive Ventilationmentioning
confidence: 99%
“…However, 15.2% of respondents were uncertain as to whether a written directive existed to guide sedation administration in their ICUs. Three sedation scale scores [Ramsay 17 (27 RT respiratory therapist; SBT spontaneous breathing trial the verbal component of the GCS (24.7%), assigning a verbal score of 1 (15.5%), or prioritizing verbal scores of 1, 3, and 5 (14.4%) in computing the GCS. Twenty-nine percent of respondents confirmed that they do not calculate the GCS.…”
Section: Other Aspects Of Weaningmentioning
confidence: 99%